Acknowledging religion in cognitive behavioural therapy: the effect on alliance, treatment expectations and credibility in a video-vignette study - Hassan, H; Lack, S; Salkovskis, PM; Thew, GR (Wiley, 2024)
Objectives: Developing mental health services which are accessible and acceptable to those from minority backgrounds continues to be a priority. In the United Kingdom, individuals who identify with a religion are underrepresented in Talking Therapies services as compared to those with no religion. This necessitates an understanding of how therapy is perceived. This online study explored the impact of explicitly acknowledging religion on anticipated alliance, treatment credibility and expectations of therapy in a non-clinical sample of British Muslims.